Rituximab in Combination With Bortezomib, Plasmapheresis, and High-Dose IVIG to Treat Antibody-Mediated Renal Allograft Rejection. Issue 8 (August 2016) - Waiser, Johannes; Duerr, Michael; Schönemann, Constanze; Rudolph, Birgit; Wu, Kaiyin; Halleck, Fabian; Budde, Klemens; Lachmann, Nils
Abstract : Background: Current treatment strategies for antibody-mediated renal allograft rejection (AMR) are not sufficiently effective. In most centers, "standard of care" treatment includes plasmapheresis (PPH) and IVIG preparations. Since several years, modern therapeutics targeting B cells and plasma cells have become available. We investigated, whether combined administration of rituximab and bortezomib in addition to PPH and high-dose IVIG is useful. Methods: Between November 2011 and January 2013, we treated 10 consecutive patients with biopsy-proven AMR with rituximab (500 mg), bortezomib (4× 1.3 mg/m 2 ), PPH (6×), and high-dose IVIG (1.5 g/kg) (group A). This group was compared with a group of 11 consecutive patients treated with an identical regimen without rituximab between July 2010 and November 2011 (group B). Results: Median follow-up was 41(33-46) months in group A and 55(47-63) months in group B. At 40 months after treatment, graft survival was 60% in group A and 64% in group B, respectively ( P = 0.87). Before and after treatment, serum creatinine, estimated glomerular filtration rate, and proteinuria were not different between groups. A significant reduction in donor-specific HLA antibody mean fluorescence intensity was observed in group A (25.2%, P = 0.046) and B (38.3%, P = 0.01) at 3 months posttreatment. In group A, more patients suffered from side effects compared with group B (infections: 70% vs 18%, P = 0.02). Conclusions: The addition of rituximab to bortezomib, PPH, and high-dose IVIG did not further improve graft survival. Instead, we observed an increase of side effects. Therefore, combined administration of bortezomib and rituximab in addition to PPH and IVIG should be regarded with caution.